Pengaruh Komunikasi Efektif terhadap Kemampuan Bahasa Anak Usia 4-5 Tahun di RA Al Falah Simpang Kabupaten Tasikmalaya - Nuraeni, Fitri; Khomaeny, Elfan Fanhas; Nugraha, Fajar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Communication skills are a form of language development possessed by early childhood. Through communication, children can express their feelings and opinions. The language skills of early childhood communication at RA Al Falah Simpang have only reached 20% based on developmental achievements in STPPA so it is necessary to provide direction and habituation to using effective communication that is directed and consistent. This study aims to determine the effect of effective communication on the language development of children aged 4-5 years at RA Al Falah Simpang. The research method used is the experimental method using two groups, namely the experimental class and the control class. Treatment using effective communication was carried out to the experimental class in 12 meetings while the control class used conventional learning as usual. The findings obtained during the 12 meetings based on posttest data from the experimental class and the control class showed a significance value of 0.000 <0.05 that there was a significant difference between the two groups. The results of the comparison of the average values of the experimental class and the control class show that the value of the experimental class is greater than the control class, where the experimental class has an average value of 55.17 while the control class is 34.50. So it can be concluded that effective communication has a positive effect on the language skills of children aged 4-5 years at RA Al Falah Simpang.